A Confederação Operária Brasileira como expressão do Sindicalismo Revolucionário no país - Bombonatto, Inajara Allgayer Dias (2021)
This dissertation investigates and analyzes the role of anarchism in the formation process of the Brazilian Workers' Confederation through the social vector of Revolutionary Intention Syndicalism. The study is of a bibliographic nature and uses as a method the analysis of documents and official resolutions of the Brazilian Workers' Confederation produced in its congresses and meetings, as well as publications of its official press organization, the newspaper “A voz do Trabalhador”. The time frame of the study is located in the period from 1889 to 1930, examining the context of emergence of the salaried class in Brazil of the First Republic. The work is structured around three chapters that present theoretical and conceptual reflections on the constitution of the wage society and the emergence of the Brazilian labor movement, analyzing the country's social, economic and political formation. Likewise, the text discusses the expression of anarchism in Brazil, demonstrating the confluence of its ideas in syndicalism organizing experiences. The research deals with the strategies and forms of struggle of the Brazilian Workers' Confederation, evaluating its experience as the first national union organization, indicating elements that characterize it as an expression of Revolutionary Intention Syndicalism.